2011
DOI: 10.1159/000330914
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Light Intensities on the Daily Grooming Distribution of Common Marmosets Callithrix jacchus

Abstract: The daily distribution of autogrooming was evaluated in adult marmosets submitted to different illumination intensities in the light phase of the light-dark cycle. Autogrooming and locomotor activity were monitored and the faecal cortisol level assessed as a stress indicator. The distribution of autogrooming showed two distinct tendencies: when the light intensity varied from 500 to 200 lux, a slight increase in frequency and duration was observed, while a significant decrease in both variables occurred at 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…The observation that older chimpanzees adjust their posture and extend their arms to groom at longer distances (they close the gap when applying their mouth to the skin) [ 234 , 235 , 236 , 237 ] supports the role of vision in grooming and indicates a primarily hygienic, non-social function. Consistent with a relationship between seeing and grooming, a study performed in common marmosets ( Callithrix jacchus ) living in captivity has shown that self-grooming normally depends on having adequate levels of ambient light (200–500 lux) [ 238 ]. Notably, nocturnal primates that normally groom in the dark (e.g., lorises) do not rely on vision; rather, they grip their partner’s skin with their hands and groom using their mouths [ 239 ].…”
Section: Evolution Of Alternative Anti-tick Strategiesmentioning
confidence: 96%
See 1 more Smart Citation
“…The observation that older chimpanzees adjust their posture and extend their arms to groom at longer distances (they close the gap when applying their mouth to the skin) [ 234 , 235 , 236 , 237 ] supports the role of vision in grooming and indicates a primarily hygienic, non-social function. Consistent with a relationship between seeing and grooming, a study performed in common marmosets ( Callithrix jacchus ) living in captivity has shown that self-grooming normally depends on having adequate levels of ambient light (200–500 lux) [ 238 ]. Notably, nocturnal primates that normally groom in the dark (e.g., lorises) do not rely on vision; rather, they grip their partner’s skin with their hands and groom using their mouths [ 239 ].…”
Section: Evolution Of Alternative Anti-tick Strategiesmentioning
confidence: 96%
“…While endogenous opioids (e.g., β-endorphin) have been shown to play an important role in the motivation of primates to solicit social grooming [ 230 ], investigation into the motivation to perform social grooming could reveal alternative neurochemical pathways [e.g., possibly dopamine, given its role in reward-based mechanisms [ 327 ]]. The role of visualization in chimpanzee social grooming can be tested by observing the relationship between grooming behaviour and light [ 238 ], with the expectation that chimpanzees orient themselves to maximize their light source and that they avoid grooming in shadows. The study of terrestrial primates such as gorillas and François’ langurs, which have low social grooming times despite living on the ground, could reveal alternative non-grooming anti-tick strategies [ 328 , 329 ].…”
Section: How Can We Test This Hypothesismentioning
confidence: 99%
“…Porém, esse padrão de maior catação por parte do macho tende a se modificar durante o período que precede o parto dos filhotes, no qual a fêmea tende a inverter o padrão e catar mais do que ser catada (JABLONSKI JR., 1998). Em um outro estudo envolvendo limpeza corporal nessa espécie de sagui, mais especificamente autolimpeza, foi verificado a distribuição diária da taxa de exibição desse comportamento em animais adultos sob condições de cativeiro (LAMPERT et al, 2011). Os resultados mostraram que, em situações de baixa intensidade de luz (10 a 100 lux), os animais tendem a diminuir a frequência de autolimpeza, pois dependem, basicamente, da visão para exibir o comportamento (MENEZES et al, 1994).…”
Section: Comportamento De Cataçãounclassified
“…Os resultados mostraram que, em situações de baixa intensidade de luz (10 a 100 lux), os animais tendem a diminuir a frequência de autolimpeza, pois dependem, basicamente, da visão para exibir o comportamento (MENEZES et al, 1994). Verificou-se, também, que os níveis de cortisol fecal tenderam a aumentar nos animais submetidos a tais condições e, embora não tenham sido conclusivos, os resultados abriram um caminho interessante para o estudo do efeito do cativeiro na saúde desses animais (LAMPERT et al, 2011). Os autores sugeriram que os saguis em cativeiro fossem mantidos em ambientes com pelo menos 200 lux de intensidade, permitindo que os animais mantenham a autolimpeza em níveis suficientes para reduzir o desconforto causado pelo cativeiro e possível isolamento (LAMPERT et al, 2011).…”
Section: Comportamento De Cataçãounclassified